California Bearing Ratio (CBR) improvement of Kuantan clay subgrade using glass waste as stabilizer - Cheok, Chin Loong (2012)
Cement and lime are commonly used for soil stabilization. These materials are expensive and it directly increase the construction cost, the usage of recycle material is an ideal choice to overcome this problem. The objective of this project is to study the applicability and effectiveness of Glass waste in order to stabilize soil that is obtains from the subgrade. These studies involve two major studies, the engineering properties of soil before mixing with additives and strength of the soil after mixing with Glass waste. California Bearing Ratio test were conducted to obtain the CBR value of the stabilize soil. The CBR value increased mainly depends on Glass waste content. The variation content of Glass waste is 0%, 4%,.8%, 12%. Key Word: (Soil Stabilization, Glass Waste, CBR, Clay)